توريث الطفل المتبنى في قانون الميراث الخاص بمسلمي سريلانكا: دراسة فقهية تحليلية: Inheritance of Adopted Child in Muslim Intestate Succession Law of Sri Lanka: An Analytical Juristic Study - Mohammed Jiffry, Mohammed Arafath Careem; Mohamed Ali Zaroum, Abdul اHamid; Awang, Abdul Bari (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص تهدف هذه الدراسة بصورة أساسية إلى التعرض لقضايا الميراث في القانون الخاص بمسلمي سريلانكا من خلال استقراء النصوص القانونية المتعلقة بها حيث تتركز الدراسة على التعرف على مدى تطبيقات الشريعة في قضايا الإرث. وقد تبين من خلال هذه الدراسة أن الأقلية المسلمة السريلانكية تسري عليها أحكام الشريعة فيما يخص قضايا الإرث كتوريث المتبنى، حيث تم صدور القرار عن المحكمة العليا بشأن قضايا توريث المتبنى بأن المتبنى لا يقر له بحق الوراثة حسب قانون الميراث الخاص بالمسلمين المعتمد على الشريعة الإسلامية. وتتضمن الدراسة المبحثين، وبالنسبة للمبحث الأول يتناول نبذة تاريخية لقانون الميراث الخاص بمسلمي سريلانكا وتعريف المواد القانونية المتعلقة بالميراث، ويتحدث المبحث الثاني عن تطبيق الشريعة في قضية توريث المتبنى على مسلمي سريلانكا. وتعتمد الورقة البحثية على المنهج الاستقرائي في تتبع المواد القانونية المتعلقة بالميراث من مصادرها ومراجعها المناسبة، والمنهج التحليلي في الشرح والاستدلال والمناقشة. تمكن الباحث بعد استقراء قضايا الميراث وتوريث المتبنى في القانون السريلانكي، بالإضافة إلى تحليل النصوص الشرعية والقانونية المتعلقة بالموضوع من التوصل إلى أهم النتائج، منها، أولا: يتم السماح للأقلية المسلمة في سريلانكا بتنفيذ الأحكام الخاصة بالميراث كما ورد في الفقه الإسلامي، والذي يسمى بقانون الميراث الخاص بالمسلمين رقم 10 لعام 1931م. وثانيا: قد تم صدور القرار عن المحكمة العليا في سريلانكا بأن الطفل المتبنى لا يستحق الميراث من مال المتبني المسلم وفق قانون الميراث الخاص بالمسلمين المعتمد على الشريعة الإسلامية، مع أن قانون التبني السريلانكي الذي ضم كافة المواطنين السريلانكيين من المسلمين وغيرهم، أجاز توريث المتبنى في المادة السادسة. وهذا يدل على أن أحكام الشريعة تطبق على القضايا المتعلقة بالميراث بين المسلمين. وثالثا: يقتضي قانون الميراث الخاص بالمسلمين رقم 10 لعام 1931م المواد الإضافية التي تتعرض لأحكام الشريعة في الميراث حتى لا يكون هناك غموض في تطبيقه. Abstract The main focus of this study is to examine the law of Inheritance as applied to the Muslim community in Sri Lanka where the community constitutes the second largest minority of the total population of the country, through systemized research conducted in the area of Fiqh and on the relevant existing law of the nation. Thus, the research mainly involves the inconsistencies or differences between two distinct legal regimes, i.e., Islamic jurisprudence and the state's statutory law in the field specified above. The research has revealed that matters related to the Inheritance of Muslims will be dealt with in accordance with the Islamic jurisprudence, while common law is applied when testacy matters are involved. It has been established by the supreme court of Sri Lanka that a child adopted by Muslim parents would not be entitled to become their heir as the matter is governed by the Act legislated in compliance with the principles of the Islamic jurisprudence. This paper contains two matters; firstly, it deals with a historical background of the Muslim intestate succussion ordinance in Sri Lanka, and later exclusively examines the law which is applicable for Sri Lankan Muslims in terms of the adopted child inheritance in light of Islamic jurisprudence. Induction and textual analysis have been employed in this work in order to scrutinize the law relating to intestate succession and Islamic jurisprudence. This investigation concludes with three remarkable points as follows: First, Sri Lankan Muslim minority community has a right to apply Islamic law in terms of intestate succussion as per section no10, 1931. Next, in spite of the adoption ordinance being applicable to all Sri Lankans, which permits inheritance rights to an adopted child, is not applicable to the Muslims according to the Supreme Court, referring to Muslim intestate succession law which does not allow inheritance rights to an adopted child. Last, the existing Muslim intestate succession law requires some details that provide clear ideas regarding the law to avoid misinterpretation and needs to be reformed.